Reconstructing palaeoenvironmental conditions faced by Mousterian hunters during MIS 5 to 3 in southwestern France: A multi-scale approach using data from large and small mammal communities. (17th March 2017) - Discamps, Emmanuel; Royer, Aurélien
Abstract: Evaluating the impact of climate change on Neanderthal groups is frequently hindered by the lack of adequate palaeoenvironmental data. Here, we explore how data concerning large and small mammal communities can be used to reconstruct environmental conditions confronted by Mousterian hunters during MIS 5 to 3 in southwestern France. Ungulate and rodent faunas are analysed using a GIS database integrating 212 faunal assemblages from 44 archaeological and paleontological sequences, revealing considerable geographical and chronological variability in terms of composition. Faunal proxies (small and large mammals) from different types of accumulations (archaeological assemblages, hyena dens and natural traps) are then compared with other independent environmental proxies (marine core, stalagmites). Our results highlight how proxies can differ, notably by reconstructing environmental conditions at distinct geographical scales (local, sub-regional, regional), and how their cross-scale comparison can aid environmental reconstructions of terrestrial ecosystems. The complex response of faunal communities to climate changes suggest that environmental reconstructions at local and sub-regional scales are required before discussing the influence of the environment on Neanderthal behavioural and cultural evolution.